Late peri-stent contrast staining appearance due to rupture of atherogenic neointima following drug-eluting stent - Tamaru, Hiroto (J Cardiol Cases, 2020)
The development of peri-stent contrast staining (PSS) after coronary intervention with implantation of a stent is observed in approximately 1–3% of patients treated with drug-eluting stent. Although the cumulative incidences of late in-stent restenosis and stent thrombosis are significantly higher in lesions with PSS than in those without the finding, the mechanisms for the development of PSS have not yet been fully elucidated. In this report, we describe a case of rapid development of PSS with ulcer formation caused by rupture of atherogenic neointima, which was observed by serial optical coherence tomography examinations over 6 months. Protrusion of the stent-jailed underlying necrotic core toward the lumen by the contracting force might have resulted in formation of atherogenic neointima within the stent. Subsequently, rupture of this necrotic core induced by iatrogenic neointimal injury due to balloon dilation and dissolution of the accumulated necrotic core may have resulted in PSS formation 6 months after the procedure. These findings may be helpful for consideration of etiology and therapeutic strategy for lesions with PSS. <Learning objective: The mechanisms of peri-stent contrast staining (PSS) formation late after drug-eluting stent (DES) implantation are diverse. Rupture of atherogenic neointima with subsequent dissolution of the stent-jailed underlying plaque debris could be one of the mechanisms of rapid PSS formation after implantation of DES. An accurate assessment of lesion morphology within the stent and patient-tailored management can reduce morbidity and mortality in patients who have undergone DES implantation.>